Signal processing and control system for the Antarctic peruvian MST radar - Sarango, Martín F. (1995)
This paper describes a signal processing and control system, designed and built in collaboration between Jicamarca Radar Observatory and University of Piura, Peru, for the peruvian MST radar installed in the "Machu-Picchu" Scientific Station, Antarctica (62 05'5 S, 58 28' W). An identical system has been built for the Jicamarca Unattended Long-term Investigations of the Atmosphere (JULIA) project.